Global compositional and functional states of the human gut microbiome in health and disease - Lee, Sunjae; Portlock, Theo; Le Chatelier, Emmanuelle; Garcia-Guevara, Fernando; Clasen, Frederick; Oñate, Florian Plaza; Pons, Nicolas; Begum, Neelu; Harzandi, Azadeh; Proffitt, Ceri; Rosario, Dorines; Vaga, Stefania; et al. (Genome Research, 2024)
The human gut microbiota is of increasing interest, with metagenomics a key tool for analyzing bacterial diversity and functionality in health and disease. Despite increasing efforts to expand microbial gene catalogs and an increasing number of metagenome-assembled genomes, there have been few pan-metagenomic association studies and in-depth functional analyses across different geographies and diseases. Here, we explored 6014 human gut metagenome samples across 19 countries and 23 diseases by performing compositional, functional cluster, and integrative analyses. Using interpreted machine learning classification models and statistical methods, we identified Fusobacterium nucleatum and Anaerostipes hadrus with the highest frequencies, enriched and depleted, respectively, across different disease cohorts. Distinct functional distributions were observed in the gut microbiomes of both westernized and nonwesternized populations. These compositional and functional analyses are presented in the open-access Human Gut Microbiome Atlas, allowing for the exploration of the richness, disease, and regional signatures of the gut microbiota across different cohorts.